2012
DOI: 10.3736/jcim20121208
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of clinical indices in syndrome differentiation of chronic hepatitis B: an exploration based on receiver operating characteristic curves and stepwise discriminant analysis

Abstract: Neither single differential index nor multiple differential indices determinant models provided appropriate determination of the TCM syndromes of patients with chronic hepatitis B, suggesting that clinical indicators have limited value in determining traditional Chinese medicine syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…As was shown in Tables 4, 5, and 6, there is no significant correlation between most metabolites and clinical indicators except for minority indexes, which may illustrate little relationship between the objective material basis related to tongue coating and the clinical indicators. Our earlier study showed that the clinical indicators had limited value in determining TCM syndromes in patients with chronic hepatitis B [38]. In addition, among these clinical indicators there were no significant differences between Group A and Group B.…”
Section: Discussionmentioning
confidence: 98%
“…As was shown in Tables 4, 5, and 6, there is no significant correlation between most metabolites and clinical indicators except for minority indexes, which may illustrate little relationship between the objective material basis related to tongue coating and the clinical indicators. Our earlier study showed that the clinical indicators had limited value in determining TCM syndromes in patients with chronic hepatitis B [38]. In addition, among these clinical indicators there were no significant differences between Group A and Group B.…”
Section: Discussionmentioning
confidence: 98%
“…For example, syndromes of liver depression, damp heat and blood stasis can be often perceived in SD patients 9 . Epidemic studies indicated that the most common complex syndromes in HBV-infection patients were accumulated dampness-heat syndrome (ADHS), spleen deficiency with liver depression (SDLD) and blood stasis vessel obstruction syndrome (BSVO) 10,11 . The complex syndrome phenotypes pose a great challenge to differential diagnosis.…”
Section: Traditionalmentioning
confidence: 99%